Development Of Prefabricated Building Implementation Frame Work For Addressing Housing Needs In Libya - El Abidi, Khaled M Amtered (2018)
Addressing housing needs is of great concern in many countries of the world with more predominance in developing countries and Libya is not an exception. Related literature has proven that prefabricated building can help improve housing delivery efforts in terms of speed, quantity, and quality as well as post-conflict reconstruction. This research is concerned with prefabricated building in Libya, which has not been investigated before. A mi.xed methods approach was developed for this purpose, with emphasis given to qualitative research techniques. Methods used comprised: .secondary data, semi-structured interviews, quantitative survey, AHP survey, and focus group discussions. Qualitative research methods offered an exploration in the first stage. Whereas quantitative research methods contributed to a more rigorous interpretation process in the second stage, qualitative research methods offered a solid description of the former. Fhe findings of the early stages of this study have shown that the participants of semi-structured interviews' have recognized prefabricated building benefits on addressing housing needs, eventhough they are not entirely sure about the method of implementation. In order to establish a comprehensive understanding on CSFs for prefabricated building implementation, exploring another country with an established industry, such as Malaysia, is necessary. From the identified CSFs, a conceptual framework that is able to comply with the construction industry needs in Libya is developed via focus group. Ten CSFs were identified under three main elements: strategy, process, and people, followed by three important sources of funding factors and three major enabling factors, f^esults from this study concur with previous studies regarding the importance of the country's political stability and its policies towards new investment and infrastructure.